KAJIAN GUGUS FUNGSI DAN KOMPOSISI MINERAL BATUAN TERALTERASI MENGGUNAKAN SPEKTROSKOPI SEM-EDX DAN FTIR PADA DAERAH MANIFESTASI PANAS BUMI DI DESA TORAGET, LANGOAN, KABUPATEN MINAHASA - Rizaldy Lasut; Donny Royke Wenas (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
North Sulawesi is one of the regions with a large potential of geothermal manifestations, wrongly located in Toraget Village, District of Langoan, Minahasa Regency, where there is a geothermal manifestasion . The purpose of this study was to study the mineral composition using SEM-EDX and FTIR in Toraget Village, Langoan District, Minahasa Regency. Based on the results of research conducted in Toraget Village, Langoan District, Minahasa Regency has a mineral composition in sample 1 namely Oxygen (O), Silica (Si) with percentages of weight are 61.32% and 38.68% and atomic percentages respectively 73.57% and in sample 2 hot springs have elemental content that is Oxygen (O) with percentage weight and percentage atomic 100%. For the functional cluster of rock sample 1 which contains C-O Ester, C-H Alkene, Aromatic C=C Alkene, and sample 2 contains C-O Esters, C-H Alkene, Aromatic C=C Alkene.